The Trypanosoma cruzi satellite DNA OligoC-TesT and Trypanosoma cruzi kinetoplast DNA OligoC-TesT for diagnosis of Chagas disease: a multi-cohort comparative evaluation study. - Koen De Winne; Philippe Büscher; Alejandro O Luquetti; Suelene B N Tavares; Rodrigo A Oliveira; Aldo Solari; Ines Zulantay; Werner Apt; Patricio Diosque; Mercedes Monje Rumi; Nuria Gironès; Nuria Gironès; et al. (Public Library of Science (PLoS), 2014)
BACKGROUND: The Trypanosoma cruzi satellite DNA (satDNA) OligoC-TesT is a standardised PCR format for diagnosis of Chagas disease. The sensitivity of the test is lower for discrete typing unit (DTU) TcI than for TcII-VI and the test has not been evaluated in chronic Chagas disease patients. METHODOLOGY/PRINCIPAL FINDINGS: We developed a new prototype of the OligoC-TesT based on kinetoplast DNA (kDNA) detection. We evaluated the satDNA and kDNA OligoC-TesTs in a multi-cohort study with 187 chronic Chagas patients and 88 healthy endemic controls recruited in Argentina, Chile and Spain and 26 diseased non-endemic controls from D.R. Congo and Sudan. All specimens were tested in duplicate. The overall specificity in the controls was 99.1% (95% CI 95.2%-99.8%) for the satDNA OligoC-TesT and 97.4% (95% CI 92.6%-99.1%) for the kDNA OligoC-TesT. The overall sensitivity in the patients was 67.9% (95% CI 60.9%-74.2%) for the satDNA OligoC-TesT and 79.1% (95% CI 72.8%-84.4%) for the kDNA OligoC-Test. CONCLUSIONS/SIGNIFICANCE: Specificities of the two T. cruzi OligoC-TesT prototypes are high on non-endemic and endemic controls. Sensitivities are moderate but significantly (p = 0.0004) higher for the kDNA OligoC-TesT compared to the satDNA OligoC-TesT.